2014
DOI: 10.1002/2014jb011346
|View full text |Cite
|
Sign up to set email alerts
|

Full‐3‐D tomography for crustal structure in Southern California based on the scattering‐integral and the adjoint‐wavefield methods

Abstract: We have successfully applied full-3-D tomography (F3DT) based on a combination of the scattering-integral method (SI-F3DT) and the adjoint-wavefield method (AW-F3DT) to iteratively improve a 3-D starting model, the Southern California Earthquake Center (SCEC) Community Velocity Model version 4.0 (CVM-S4). In F3DT, the sensitivity (Fréchet) kernels are computed using numerical solutions of the 3-D elastodynamic equation and the nonlinearity of the structural inversion problem is accounted for through an iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
258
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(295 citation statements)
references
References 127 publications
27
258
2
Order By: Relevance
“…http://gji.oxfordjournals.org/ Downloaded from Lee et al 2014) and have been interpreted as rocks of the Peninsula Ranges batholith (Lutter et al 1999). We also note the depression of the velocity contour in the 3-6 km depth range at 10 km distance.…”
Section: The Shear Velocitiesmentioning
confidence: 58%
See 2 more Smart Citations
“…http://gji.oxfordjournals.org/ Downloaded from Lee et al 2014) and have been interpreted as rocks of the Peninsula Ranges batholith (Lutter et al 1999). We also note the depression of the velocity contour in the 3-6 km depth range at 10 km distance.…”
Section: The Shear Velocitiesmentioning
confidence: 58%
“…The high velocity basement has been previously revealed in V P (Lutter et al 1999;Fuis et al 2001;Lee et al 2014), which can be higher than 7 km s −1 in some locations (Lutter et al 1999; at California Institute of Technology on August 19, 2016…”
Section: The Shear Velocitiesmentioning
confidence: 85%
See 1 more Smart Citation
“…The Los Angeles Basin is a typical example of this, where there have been many studies of its structure (Hauksson & Haase 1997;Fuis et al 2001;Süss & Shaw 2003;Tape et al 2009;Lee et al 2014;Shaw et al 2015), using data from both passive and active seismic experiments, as well as well-logs and reflection data from the oil industry. The culmination of these efforts has been the creation of a series of steadily improving Community Velocity Models (Kohler et al 2003;Plesch et al 2011;Shaw et al 2015), which are used among other things, in the simulation of ground motions from scenario earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limiting computational power and the complexity of the forward solver, most of the applications in this domain are in 2D rather than 3D, and acoustic or visco-acoustic rather than visco-elastic; although recent applications with 3D elastic algorithms were reported in the literature (e.g. Lee et al, 2014). Several successful applications of fullwaveform tomography ranging from crustal studies using wide angle refraction data to reflection seismic can be found in the literature (e.g., Takam Takougang and Calvert, 2011, Mallinowski et al, 2011Kamei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%